Implementasi Teknologi Augmented Reality Dalam Pembelajaran Tajwid Kelas 5 Pada Hukum Bacaan Mim Sukun Dan Tanwin Berbasis MDA Framework - Faisal Reza Pradhana; Triana Harmini; Hanifa Ramadhani Ayuningrum S (LPPM UBHINUS MALANG, 2023)
Tajwid learning at SD Birrul Walidain Muhammadiyah Sragen currently relies in person or Direct interaction between educators and learners, using textbooks as the primary source of material. However, the results of observations revealed that there were weaknesses in the methods currently used, especially in learning the science of recitation, where from the results of the pretest carried out on students, 79.41% of them got a score below 50 (grade scale 1-100). This research aims to design a learning application for the rules of reading